Social Profile of Elderly In Al -Gadarif Region in Eastern Sudan: 2014-2015. (Journal of Basic and Applied Research in Biomedicine, 2022)
Population ageing is a current phenomenon that occurs worldwide due to improved standard of life and health care and services in most of the world countries. In recognition of this phenomenon, geriatric education was recently introduced as part of medical and health sciences. The overall objective of the study to assess the health status and factors affect the health of elderly 65 years and above in El Gadarif region (locality) in Eastern Sudan. This was descriptive cross-sectional study conducted in ElGedarif region. Data were collected by using standardized interview questionnaire for 388 participants. Statistics analysis was done using SPSS and chi-square test. The survey findings showed that 8.4% of the participants of the survey required assistance on eating, 9.5% , on bathing, 8.8%on dressing, while 46.4% required assistance on shopping, and 25% on taking medication. The findings also showed that 45.6% of the participants spent time watching T.V, 44.6% listening to radio, 48.4% engaging in interpersonal communication, and 14.8% reading. Chi-square results for testing significant relationship between taking medication and hypertension showed (P Value 0.06), the equivalent results between chronic disease and assistance in shopping was P value=0.000, between health status and exercise sports was ( p-value 0.000)and between Exercise Sports and sufficient sleep was ( P Value: 0.0). The results of the study reflected the very crucial role of the family in supporting the elderly in El Gadarif region, and showed that most of the participants were able to practice their daily life (routine) activities by themselves.